2012
DOI: 10.1016/j.concog.2012.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysics of EEG alpha state discrimination

Abstract: Nearly all research in neurofeedback since the 1960s has focused on training voluntary control over EEG constructs. By contrast, EEG state discrimination training focuses on awareness of subjective correlates of EEG states. This study presents the first successful replication of EEG alpha state discrimination first reported by Kamiya (1962). A 150-second baseline was recorded in 106 participants. During the task, low (<30th percentile of the baseline) and high alpha events (>70th percentile) triggered a prompt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
4
19
1
Order By: Relevance
“…The five criterion sessions had a mean 4.4 days since the previous session, compared to 8.2 for the remaining sessions (previously seen in Frederick, 2012). A similar effect was not seen for the control task.…”
Section: Referencesmentioning
confidence: 49%
See 1 more Smart Citation
“…The five criterion sessions had a mean 4.4 days since the previous session, compared to 8.2 for the remaining sessions (previously seen in Frederick, 2012). A similar effect was not seen for the control task.…”
Section: Referencesmentioning
confidence: 49%
“…Arnstein, D., Cui, F., Keysers, C., Maurits, N. M., & Gazzola, V. (2011 It is commonly argued that the mechanism of action of biofeedback involves increasing awareness of subjective correlates of one's physiological state (Frederick, 2007(Frederick, , 2012. However, the relationship between awareness and control of physiological states is largely unexplored.…”
Section: Referencesmentioning
confidence: 99%
“…The discrimination task performances correlated significantly with performance in the amplitude control task. Evidence that some subjects can use the intertrial interval (ITI) to predict the correct responses in the discrimination task led to an examination of how ITIs were distributed with respect to success (correct or incorrect) and type of trial (same or different from previous) in these and 40 additional subjects from archival data (Frederick, 2012). This analysis found that some information about the correct responses was conveyed by the ITI, but participants made relatively little use of this information.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the present study, the minimum ITI was set for 8.1 s, and the null hypothesis was that there would be no advantage to perseverative responding on short ITI trials. To allow further comparison, the same hypothesis was examined in archival data (Frederick, 2012) from 40 subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Pavlov theory of conditioned reflexes and its development in the studies devoted to human EEG operant conditioning [2]. Due to the researches showing the capabilities of voluntary rearrangement and overfitting of brain wave patterns using a conditioning principle there was formed a biocontrol technology with feedback by EEG, or neurofeedback (NFB) [3].…”
mentioning
confidence: 99%